Religious Harmony within Framework of Adat Tapsila of The Sasak Islamic and Buddhist Communities in Lombok.: STUDI PADA MASYARAKAT SASAK ISLAM DAN BUDDHA DI LOMBOK - Raden Rachmy Diana; Sepma Pulthinka Nur Hanip (Jurnal Masyarakat dan Budaya, 2022)
This research is supposed to deeply observe about adat tapsila as social norm of Buddhist and Moslem citizensin Tegal Maja, North Lombok regency, with the goal supposed of religious harmony in Lombok being saved, whichbelieved as inherit cultural ethics from a period to the other period of Sasak’s tribe. The research on religiousharmony were not the recent observation, especially in Indonesia. Moreover, both generally and specificallyin Lombok, according to the prior research, religious harmony is observed by considering ritual adat aspect.There was involved the roleplay of every position such as religion subject as central of peace, Government has aposition and roleplay a creator of Community of Communication on Religious subject Institution. The researchmethodology being used were qualitative methodology with ethnography approach while humans placed basedon their environment context being observed. This study is supposed for deeply dig about adat tapsila as an ethicsand social norm while save the religious harmony, and the existence of adat tapsila for saving social integrationin plural citizens especially in Lombok.